136 Hyperthermic intraperitoneal chemotherapy for gynecologic malignancies in a community-based comprehensive cancer center: A review of morbidity and experience. (13th November 2020) - Meelheim, B; Deng, L; Wagreich, A; Gattoc, L; Tchabo, N; Harrison, L; Tobias, D
Abstract : Objectives: The combination of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to improve progression free and overall survival in ovarian cancer. Limited studies exist investigating the safety and feasibility of HIPEC implementation in a community-based setting. Our study aims to explore HIPEC use in this setting. Methods: All patients who received HIPEC at the time of cytoreductive surgery within a community-based comprehensive cancer center from 2018 through 2019 were retrospectively identified. Demographics, tumor characteristics, chemotherapy, surgical interventions, and 30-day postoperative morbidity and mortality data were collected. Results: 18 patients underwent cytoreduction and HIPEC. Most patients had stage III or IV disease (88.9%) and high grade serous ovarian carcinoma (77.8%). Two-thirds of patients received neoadjuvant chemotherapy, while one-third underwent primary cytoreduction. Cisplatin was used for HIPEC in all patients, with a median dose of 75 mg/m2 (range 50–100 mg/m2). Grade 3 and Grade 4 adverse events within 30 days of surgery occurred in 61.1% and 5.6% of patients, respectively. Adverse events included electrolyte disturbances (44.4%), gastrointestinal disorders (22.2%), hematologic alterations (16.7%), and/or infections (16.7%). There were no postoperative mortalities. Median length of hospital stay was 8 days (range 4–31), with no difference for patients with grade 3 or 4 events compared to patients with none. Conclusions: The addition of HIPEC to cytoreductive surgery had low perioperative morbidity and no mortality. Grade 3 or 4 adverse events had minimal clinical significance. This preliminary review demonstrates safe utility of HIPEC treatment for gynecologic oncology patients in a community-based comprehensive cancer center.